Haptic body position improver during a workout (International Journal of Engineering and Computer Science, 2023)
Fitness is one of the popular physical activities performed individually most of the time. While doing an activity, if the proper posture is not adopted, it can result in major injury that makes it difficult to lead a healthy life. By adopting wearable technology and haptic technology not only correct motion could be achieved but also damages due to wrong motion could be prevented. In this article we introduce a simple and convenient wearable device that can sense the position of the body during the exercise and provide haptic feedback if an improper motion was performed. The wearable system includes four gyroscopes and four coin types of vibration motors. The body position was recorded using gyroscopes and haptic feedback was applied using vibration motors. To test the system three positions were chosen and tested on five participants. The results show that the device can be used by people to have an injury-free activity where a coach is not available. Using wearable technology accompanied by the haptic feedback will improve the skills and will lead to an injury free exercise.